Pemanfaatan Hak Otonomi Daerah dalam Pengelolaan Wilayah Laut atau Pantai di Jakarta, Indonesia - Sri Herowanti Susilo (Neolectura, 2022)
An attempt to utilize marine areas based on Law no. 32 in 2004, it concerns about the Regional Government which contains the regional authority to manage their marine areas. Such authority is as stated in Article 18 paragraph (1), “they are; exploration, exploitation, conservation and marine management”. In order for regional autonomy to have a positive impact on the management of coastal/marine areas, it requires a commitment from the local government and the community in managing the marine sector in their jurisdiction to gain added value or a strategic role on an ongoing basis. Law No. 32 in 2004 has been changed to Law no. 23 in 2014, Article 14 paragraph (6).